A influência da espiritualidade, religiosidade, ansiedade e depressão na motivação dos acadêmicos de uma universidade federal - AMARO, Elisângela de Assis (2018)
Taking into account the difficulties and demands experienced in the university context and the factors that may favor school dropout, which may or may not be directly related to academic motivation, it becomes important to understand the subject in this context. This study aimed to analyze the sociodemographic, academic, spirituality, religiosity, anxiety and depression variables on the academic motivation of the Federal University of Triângulo Mineiro. It is an analytical, observational study model, with a design of the type (transversal), with quantitative approach. The research was carried out in the dependencies of the Federal University of the Triângulo Mineiro with academics of the 28 courses offered by the university. A total of 219 academics participated in the study. The research instrument consisted of two ways of the ICF and five self - applied instruments, such as the Sociodemographic Assessment Questionnaire, the Academic Motivation Scale, the Spirituality Self Rate Scale, the Duke - DUREL Scale of Religiosity, the Anxiety and Depression Scale for General Hospital - HAD. This research was approved by the CEP / UFTM Research Ethics Committee, opinion number 1,900.668. The data were entered in an EXCEL® spreadsheet, in double entry, for consistency checking. Then they were exported to the SPSS application (Statistical Packge for the Social Science), version 20.0, for statistical analysis. Categorical variables were presented in absolute and relative frequency tables, while the quantitative variables were summarized using central (mean and median) and variability or dispersion measures (amplitude and standard deviation). In the linear regression analysis according to the decreasing domain order, it was identified that the declared non-depressive academics presented weak positive statistical significance for the MIC domains β= 0,172 (p= 0,012); MIR β= 0,234 (p=<0,001); MIEE β= 0,171 (p= 0,013); MEID β= 0,248 (p= <0,001). In this way the non-depressed academics presented different states of motivation, whether controlled or autonomous, closer to self-determination. For the AMO domain it presented weak negative statistical significance β= -0,398 (p= <0,001). Academics who have declared themselves to be depressed have lower demotivation scores, that is, lower self-determination. Female subjects had a weak positive statistical significance for the domain MEID β= 0,204 (p= 0,002), thus being female influenced in MEID (controlled motivation) characterized by a lower control feeling. For nonreligious scholars, a weak negative statistical significance for the MERE domain β= - 0,302 (p= <0,001) was observed, thus, a higher motivation for expectation of reward or punishment. As a limitation of the study, there was no literature supporting the linear regression analysis for the EMA domains and even the predictors that influenced it. Thus, depression was identified as the main predictor, followed by religion and sex, but further studies are still needed to study more deeply about this topic, since several factors may interfere in the process of academic motivation.